Carbon accounting for sustainability and environmental management : case studies from China - Rana, Tarek; Rahman, Md. Jahidur; Öhman, Peter, 1960- (Routledge, 2025)
"As the world increasingly focuses on sustainability and climate justice, this book sets the scene by establishing the significance of carbon accounting in today's environmental management practices. It provides a comprehensive exploration of the subject, with a specific focus on the Chinese context and sheds light on how carbon accounting practices are being integrated into corporate and national strategies. While the book has a strong focus on empirical realities in China, its exploration of carbon accounting and environmental management holds significant international importance. The book bridges the gap between theory and practice, offering readers in-depth insights into the intricate dynamics of carbon accounting and its implications for sustainable development, drawing on data and case studies to provide practical insights into the effectiveness of various carbon accounting approaches and their impact on environmental sustainability. It focuses on the crucial role of the development of green accounting, its future growth and wider impact on climate change. Additionally, the book examines how accurately tracking and reporting carbon emissions is integral to developing effective environmental strategies and evolving environmental policies. Accompanied by real-world case studies, and actionable recommendations, this book is a valuable resource for anyone navigating the intricate landscape of carbon accounting and reporting, offering a road map to informed strategic decision-making and sustainable business practices. It will be particularly beneficial for professionals in environmental management, policy formulation, and corporate sustainability, as it translates complex carbon accounting concepts into tangible, practical strategies"-- Provided by publisher.
Keywords: Environmental auditing -- China.; Carbon dioxide mitigation -- China.; Environmental responsibility -- China.; Sustainable development -- China.; elektronické knihy; electronic books